Rousseau’s Philosophical-political Program: the Theoretical Link between the Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract - Gallo-Gómez, Juan Camilo (2021)
“Rousseau’s Philosophical-political Program: the Theoretical Link between the Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract”. This paper presents Rousseau’s political and theoretical legacy through the interpretation of his Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract, understanding both as a sole argumentative and methodological unit in his work. In order to achieve this objective, the paper explores first the normative and anthropological considerations that mark the problem of Rousseau’s political theory. From there, the main ideas of his notion of democracy will be presented. Finally, the paper concludes that Rousseau’s democratic legacy is particularly useful as a form of critique in the hegemonic context of the current liberal and representa-tive democracies.